Fanon's Les Damnés de la terre : translation, de-philosophization and the intensification of violence - Batchelor, Kathryn (Edinburgh University Press, 2015)
The influence of Jean-Paul Sartre’s Critique de la raison dialectique on Frantz Fanon’s Les Damnés de la terre can be seen in Fanon’s direct engagement with Sartre’s text as well as in the vocabulary that he adopts when discussing key ideas, particularly in the now infamous first chapter discussion of violence. In Constance Farrington’s English translation of Les Damnés, however, philosophical terms are replaced with everyday ones, and the links between Les Damnés and the Critique are obscured. In this paper I seek not only to highlight this de-philosophizing approach through a range of examples, but also to explore the ways in which these changes, combined with a number of significant mistranslations, enact a shift around Fanon’s conceptualization of violence, with far-reaching implications for the take-up of Les Damnés de la terre around the world.